Gambaran Sosial Ekonomi Etnis Tionghoa Dalam Arsip Peninggalan Sultan Syarif Kasim II (1915-1945) - Idayanti, Iik; Afriadi, Deni; Ridwan, Ridwan; Hermansyah, Hermansyah (Jayapangus Press, 2025)
This research discusses the socio-economic depiction of the Chinese ethnic group as recorded in the archives left by Sultan Syarif Kasim II (1915-1945). The Chinese ethnic group has been settled in the Siak region since the late 19th century, as evidenced by the existence of the Hock Siu Kiong temple located not far from the Siak palace. One of the sources of writing about Chinese activities can be found in the form of archival notes. The archives used are the legacy of Sultan Syarif Kasim II. Out of sixty thousand archives, there are 11,423 digital archives that the researcher obtained and processed, resulting in 57 archives concerning the Chinese ethnic group. The method used in this research is historical. The purpose of this research is to describe the socio-economic picture of the Chinese ethnic group in the archives of Sultan Syarif Kasim II. The research findings indicate that out of eight determining factors for the social economic status of individuals in society, three factors are present in the archives, namely type of occupation, position in an organization, and economic activities.